Genetic Diversity Analysis of Surface-Related Antigen (SRA) in Plasmodium falciparum Imported From Africa to China - Yang, Bo; Liu, Hong; Xu, Qin-Wen; Sun, Yi-Fan; Xu, Sui; Zhang, Hao; Tang, Jian-Xia; Zhu, Guo-Ding; Liu, Yao-Bao; Cao, Jun; Cheng, Yang (Frontiers in Genetics, 2021)
Plasmodium falciparum surface-related antigen (SRA) is localized on the surfaces of both merozoites and gametocytes, has the structural and functional characteristics of a very promising target for multistage vaccine development. However, little information is available regarding the genetic polymorphism of pfsra. To determine the extent of genetic variation about P. falciparum by characterizing the sra sequence, seventy-four P. falciparum samples were collected from migrant workers who returned to China from 12 countries of Africa between 2015 and 2019. Full-length of sra gene was amplified and sequenced. The average pairwise nucleotide diversities (π) of P. falciparum sra gene was 0.00132, and the haplotype diversity (Hd) was 0.770. The average number of nucleotide differences (k) for pfsra was 3.049. The ratio of non-synonymous (dN) to synonymous (dS) substitutions across sites (dN/dS) was 1.365. Amino acid substitutions of P. falciparum SRA could be categorized into thirty-five unique amino acid variants. Neutrality tests indicated that the polymorphism of PfSRA was maintained by positive diversifying selection, suggesting its role as a potential target of protective immune responses and a vaccine candidate. Overall, anti-PfSRA antibodies to evoke inhibition of merozoite invasion of erythrocytes and conserved amino acid at low genetic diversity suggest that N-terminal of PfSRA could be evaluated as a vaccine candidate against P. falciparum infection.